Manufacture of novel intermetallic bond coats from the electroplating of ionic liquids - Craig, Mark (Cranfield University, 2010)
Gas turbine engines for both aerospace and power generation are constantly being revised to improve running efficiency and performance. Gas turbine engines essentially consist of three distinct regions: compressor, combustion and turbine sections with the combustor and turbine sections required to experience higher and higher temperatures in pursuit of efficiency gains. Stage 1 high pressure turbine blades (buckets) are located closest to the combustion zone and experience extremely high temperatures. Further, turbine blades experience high centrifugal force whilst in operation and therefore engine designers must take into consideration both the mechanical effects o f operation and the high temperatures associated with engine use. Environmental resistant coating systems are therefore employed to allow the design of the base material (nickel-based superalloys) to be biased towards mechanical properties (high creep resistance). Nickel-platinum-aluminide coatings are the diffusion coating of choice for both aero-and industrial turbines with the platinum being typically deposited by electroplating on the nickel alloys, followed by heat treating to form a platinised enriched area which is then aluminised by insertion into a chemical vapour deposition (CVD) retort and reacting with an aluminium halide at elevated temperature. The CVD process is utilised as it is relatively easy to form desirable intermetallics though this route. The electrodeposition of aluminium from aqueous media is not possible as water undergoes hydrolysis before the reduction potential of aluminium is reached. Ionic liquids are an alternative method o f depositing aluminium via electroplating without the need o f water as the electrolyte. Ionic liquids have numerous benefits including a wide electrochemical window and have low toxicity. In comparison to the CVD process, they are multiuse and can be easily recycled/reused as the ionic liquid itself is not consumed within the plating process. Electroplating aluminium from ionic liquids to form a dense coating onto nickelbased superalloys is therefore proposed within this thesis as an alternative novel approach to achieving desirable nickel aluminide intermetallic coatings after post processing heat treatment. Furthermore, the post heat treatment may be done within either a traditional CVD-type regime or with a new and novel low temperature heat treatment regime developed as part of this thesis - ICON. Both heat treatments form β-NiAl. The heat treatment using CVD-type parameters forms coatings akin to those produced using a CVD route, whereas the ICON coating shows improved chemical homogeneity and a smaller interdiffusion zone - both o f which are shown to offer superior coating oxidation performance. Aluminium electrodeposited on CMSX4 heat treated with CVD-type parameters shows excellent cyclic oxidation data which is at least equal to, if not greater than those produced using traditional methods.